Pengaruh Senam Hamil terhadap Tingkat Depresi Ibu Hamil Trimester III di Kecamatan Sukawati - Ni Wayan Noviani; Ni Wayan Sukma Adnyani (Politeknik Kesehatan Kartini Bali, 2022)
This study aims to know the effect of pregnancy exercise on the depression level of the third trimester of pregnant woman in the Kecamatan Sukawati. This type of research is analytic with a one group pre-test post-test design without control, the number of samples is 50 pregnant women who meet the inclusion criteria by using purposive sampling technique. The instrument data collection using depression anxiety and stress scale (DASS) questionnaire. Bivariate analysis using Wilcoxon test. The result of the data shows p value of depression level of pregnant women before and after the implementation of pregnancy exercise is 0.102 (>0.05), it can be concluded that there is an no effect of the implementation of pregnancy exercise on the depression level of pregnant women in the third trimester. From the result of research conducted, the effect of the implementation of pregnancy exercise on the depression level of pregnant women before and after of pregnant women in the third trimester.